Exploring the Relationship between Visual Learning Styles and Learning Outcomes in Limnology Course: A Quantitative Descriptive Study - Raya Agni; Syech Zainal; Pahriadi; Suhendar (CV. Dharma Samakta Edukhatulistiwa, 2023)
The objective of this study is to examine the correlation between learning styles and student learning outcomes in the Limnology course within the Biology Education Study Program at FKIP UNTAD, during the odd academic year of 2021/2022. The present study employs a quantitative descriptive research methodology. The data was obtained by administering a learning style questionnaire consisting of 23 items to a sample of 30 students enrolled in the Biology Education Study Program at FKIP UNTAD. The data analysis was conducted using the Product Moment correlation test. The findings of the research indicate that during the odd semester of the 2021/2022 academic year, all students enrolled in the Limnology elective course exhibited a preference for visual learning. Nevertheless, a diminished correlation was observed in relation to the association between learning styles and student learning outcomes. The results of this study make two distinct contributions to the current body of literature. The present study describes a taxonomy of participant learning styles, making anticipatory projections based on analogous investigations. Furthermore, this study investigates the influence of different learning styles on the achievement of learning objectives. Moreover, this study incorporates demographic data to control for its impact on educational achievements. The examination and interpretation of the findings from both analyzes will enhance scholarly comprehension of the essential determinants of success in the learning process and their tangible implementation in the field of Limnology education.